PERAN DANA PINJAMAN DARI LEMBAGA PERBANKAN BAGI KELANGSUNGAN USAHA PEDAGANG PASAR TRADISIONAL BALONGPANGGANG-GRESIK - Listianah Listianah; Nurul Hasanah Uswati Dewi (Universitas Hayam Wuruk Perbanas, 2012)
Activities in the rural economy is still dominated by small businesses with the main actorsare the farmers, agricultural laborers, merchants, and home industries. They are generallystill faced with the classic problem of the limited capital available, including market tradersBalongpanggang. Balongpanggang market has become the economic center of Balongpanggangcommunity, so this condition attracted the banking institutions to provide loan funds tothe merchant market. The purpose of this study is to determine the role of loan funds in bankinginstitutions for merchant business continuity. In this research, interviews and observationsare conducted to obtain the required data. The results of this study indicate that thebanking institution has an important role for market traders Balongpanggang, especiallyloans given by banks.